Dance upon the air - Roberts, Nora (New York : Jove Books, 2001)
"When Nell Channing arrives on charming Three Sisters Island, she believes that she's finally found refuge from her abusive husband--and from the terrifying life she fled so desperately eight months ago ... But even in this quiet, peaceful place, Nell never feels entirely at ease. Careful to conceal her true identity, she takes a job as a cook at the local bookstore cafe and begins to explore her feelings for the island sheriff, Zack Todd. But there is a part of herself she can never reveal to him, for she must continue to guard her secrets if she wants to keep the past at bay. One careless word, one misplaced confidence, and the new life she's so carefully created could shatter completely. Just as Nell starts to wonder if she'll ever be able to break free of her fear, she realizes that the island suffers under a terrible curse--one that can only be broken by the descendants of the Three Sisters, the witches who settled the island back in 1692. And now, with the help of two other strong, gifted women--and the nightmares of the past haunting her every step--she must find the power to save her home, her love ... and herself"-- Provided by publisher
Keywords: FICTION Romance General ; Secret Romans, nouvelles, etc. ; Women Massachusetts Fiction